2017
DOI: 10.1016/j.prevetmed.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic disease risk perceptions in the British veterinary profession

Abstract: In human and veterinary medicine, reducing the risk of occupationally-acquired infections relies on effective infection prevention and control practices (IPCs). In veterinary medicine, zoonoses present a risk to practitioners, yet little is known about how these risks are understood and how this translates into health protective behaviour. This study aimed to explore risk perceptions within the British veterinary profession and identify motivators and barriers to compliance with IPCs. A cross-sectional study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
(63 reference statements)
1
11
0
Order By: Relevance
“…Common zoonotic diseases, which include dermatophyte (fungal) infections, are easily managed (Australian Infectious Diseases Advisory Panel, ). Infection with more severe zoonotic pathogens is considered a low risk by many veterinary staff (Robin, Bettridge, & McMaster, ; Sellens et al, ). This perception influences the lack of PPE utilized or enforced by veterinary staff (Dowd et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Common zoonotic diseases, which include dermatophyte (fungal) infections, are easily managed (Australian Infectious Diseases Advisory Panel, ). Infection with more severe zoonotic pathogens is considered a low risk by many veterinary staff (Robin, Bettridge, & McMaster, ; Sellens et al, ). This perception influences the lack of PPE utilized or enforced by veterinary staff (Dowd et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Australian veterinarians are at risk of exposure to a number of potentially fatal or debilitating chronic zoonotic diseases. Recent studies in both Australia and overseas have shown that many veterinarians do not use effective PPE [ [28] , [29] , [30] ], and the opinion of the expert panel suggests that this is still an area of concern. It is unclear why members of the expert panel did not place the same importance on PPE for GPs, given that in recent history GPs in Australia and elsewhere have also had significant risk of exposure to EIDs of zoonotic origin transmitted in healthcare settings, such as Ebola and SARS.…”
Section: Discussionmentioning
confidence: 99%
“…and was corroborated by a study involving British veterinarians, in which even with a forecast of 30% adherence, the minimum number of participants required was not reached (Robin, Bettridge, & McMaster, 2017). On the other hand, the use of online platforms makes epidemiological surveys less expensive and faster than classical methodologies.…”
Section: Discussionmentioning
confidence: 95%